Culturally tailored interventions for ethnic minorities: A scoping review - Jee Young Joo; Megan F. Liu (Wiley, 2021)
Abstract Aim This scoping review identifies strengths and weakness of culturally tailored interventions for ethnic minorities' care in the United States. It reviews recently published studies to improve understanding of these interventions for future research and practice. Design Scoping review. Methods By searching five electronic databases-CINAHL, PubMed, Ovid, Scopus and Web of Science, this review located 58 empirical studies published between 2015-2019. This review was guided by the PRISMA statements. Results The review identified four weaknesses and five strengths of culturally tailored interventions. Weaknesses included unclear guidelines, low attention and retention rates, failure to measure processes and inadequate training for healthcare providers. The intervention strengths were culturally respectful and patient‐centred care, healthy lifestyle promotion, increased family and community supports, technology use for efficient and timely care and increased knowledge of disease by participants.